Exile, Diplomacy and Texts Exchanges between Iberia and the British Isles, 1500-1767 - Sáez-Hidalgo, Ana; Cano Echevarría, Berta (Intersections, 2020)
Exile, Diplomacy and Texts offers an interdisciplinary narrative of religious, political, and diplomatic exchanges between early modern Iberia and the British Isles during a period uniquely marked by inconstant alliances and corresponding antagonisms. Such conditions notwithstanding, the essays in this volume challenge conventionally monolithic views of confrontation, providing - through fresh examination of exchanges of news, movements and interactions of people, transactions of books and texts - new evidence of trans-national and trans-cultural conversations between British and Irish communities in the Iberian Peninsula, and of Spanish and Portuguese 'others' travelling to Britain and Ireland. Readership: All interested in early modern European (British, Irish, Spanish, Portuguese) history, and its political, religious, diplomatic and cultural manifestations, also from a comparatist perspective. Keywords: ambassadors, Black Legend, book history, captives, Catholic colleges, chronicles, Early Modern, imagology, libraries, manuscript culture, networks, news pamphlets, reading culture, visual culture.